2008
DOI: 10.1159/000178165
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Saline Irrigation Facilitates Control of Allergic Rhinitis by Topical Steroid in Children

Abstract: Objective: This study was designed to determine whether nasal saline irrigation improved the symptoms and signs of allergic rhinitis (AR) and whether nasal saline irrigation could be used as a complementary management of AR in children while less steroids were used. Method: 26 children with AR were divided into three groups and were given nasal saline irrigation and/or topical steroid. Symptoms and signs of AR and mucociliary clearance (MCC) were evaluated, and concentration of soluble intercellular adhesion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 49 publications
2
48
0
4
Order By: Relevance
“…The positive effect of nasal irrigation with hypertonic saline on the clinical course of seasonal Parietaria-related AR and the need for drug administration to control its signs and symptoms has been previously demonstrated in children by Garavello et al (11,12) and Li et al (13). However, our findings extend our knowledge of the impact of nasal irrigation in children with seasonal grass pollen-related AR.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The positive effect of nasal irrigation with hypertonic saline on the clinical course of seasonal Parietaria-related AR and the need for drug administration to control its signs and symptoms has been previously demonstrated in children by Garavello et al (11,12) and Li et al (13). However, our findings extend our knowledge of the impact of nasal irrigation in children with seasonal grass pollen-related AR.…”
Section: Discussionsupporting
confidence: 83%
“…We also found that a bulb syringe can be correctly used by adequately instructed school-aged children supervised by their parents. Finally, both the children and their parents easily accepted the relatively small volume of fluid instilled twice a day, thus overcoming the problem of the need to administer larger volumes reported by some authors (13).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rinsing the nasal cavity with saline is an inexpensive method of treating rhinitis with low, but proven efficacy [23,24].…”
Section: Moisturizersmentioning
confidence: 99%
“…It permitted use of less topical steroids for controlled AR in children which will contribute to fewer side effects and less economic burden [5].…”
Section: Filtrationmentioning
confidence: 99%